2017
DOI: 10.1103/physreva.96.063417
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of strong-field-ionization theories for laser fields from visible to midinfrared frequencies

Abstract: Strong field ionization yield versus intensity is investigated for various atomic targets (Ne, Ar, Kr, Xe, Na, K, Zn and Mg) and light polarization from visible to mid-infrared (0.4-4µm), from multiphoton to tunneling regimes. The experimental findings (normalized yield vs intensity, ratio of circular to linear polarization and saturation intensities) are compared to the theoretical models of Perelomov-Popov-Terent'ev (PPT) and Ammosov-Delone-Krainov (ADK). While PPT is generally satisfactory, ADK validity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 68 publications
(83 reference statements)
1
20
0
4
Order By: Relevance
“…Our second route to determining the peak intensity implemented a fit of our data to the Perelomov-Popov-Terent’ev (PPT) 31 formulation of strong-field ionization theory. PPT was recently shown to accurately describe experimental results for multi-cycle pulses from 400 nm to 3.9 μ m 32 . Fitting our data, shown as the dashed blue line in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Our second route to determining the peak intensity implemented a fit of our data to the Perelomov-Popov-Terent’ev (PPT) 31 formulation of strong-field ionization theory. PPT was recently shown to accurately describe experimental results for multi-cycle pulses from 400 nm to 3.9 μ m 32 . Fitting our data, shown as the dashed blue line in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The apparent discrepancy between the experiments of Lai et al 48 , showing the validity of the PPT ionization rate formula, and the EID calculations can be explained by the fact that the experiments by Lai et al were conducted at low gas pressures, where the many-body interactions lose their importance. To clarify this situation, Woodbury et al 56 experimentally measured the ionization yield in air, nitrogen, and argon at atmospheric (0.5–3 bar) pressures for 1.024 and 3.9 μm picosecond laser pulses.…”
Section: Medium Responsementioning
confidence: 87%
“…To complete the semi-classical description of ionization for long-wavelength laser pulses, we have to indicate the way to calculate the corresponding ionization rate. Recently, Lai et al 48 experimentally studied the ionization yield versus laser intensity for various atomic targets irradiated by laser pulses with different polarizations and wavelengths ranging from the visible to the mid-infrared (0.4–4 μm) in both the multiphoton and tunneling regimes. The experimental findings were compared to the ionization rate calculated by the Perelomov-Popov-Terent’ev (PPT) formula 49 .…”
Section: Medium Responsementioning
confidence: 99%
“…Recently, the improved PPT model was used to calibrate the laser intensity in strong-field ionization experiments [23]. It was also demonstrated that the PPT model is fully capable of reproducing single ionization probabilities for atoms in laser fields from the multiphoton to the tunneling ion-ization regimes [24]. While the SFA1 model was used in [15,17], in the present paper we employ the improved PPT model to calculate the single ionization yield for Ne atoms.…”
Section: Theoretical Modelmentioning
confidence: 99%